Hydroxysafflor yellow A (HSYA) attenuates hypoxic pulmonary arterial remodelling and reverses right ventricular hypertrophy in rats. (20th June 2016) - Li, Lei; Dong, Pengda; Hou, Congjia; Cao, Fangyuan; Sun, Shouli; He, Fa; Song, Yanping; Li, Sen; Bai, Yuhua; Zhu, Daling
Abstract: Ethnopharmacological relevance: Carthamus tinctorius L. is a traditional herbal medicine native to China with properties of promoting blood circulation and removing blood stasis, which is used for the treatment of cerebrovascular and cardiovascular diseases. Hydroxysafflor yellow A (HSYA) is the main constituent isolated from the flower of Carthamus tinctorius L. which is used as a marker substance in the quality control of Carthamus tinctorius L. in Chinese Pharmacopeia. Aim of the study: This study is to investigate the hypertension attenuating effect of HSYA on hypoxia-induced pulmonary artery hypertension model rats, and the possible mechanism. Materials and methods: The animal models were made by treating adult male Wistar rats (of the same age with the same weight of 200±25 g) under hypoxia 24 h per day for 9 days with or without administration of HSYA. The pulmonary arterial pressure of rats was measured after anesthetization; The right ventricular hypotrophy was evaluated by the right ventricular hypotrophy index (RVHI=[RV/(LV+S)]) as well as histomorphology assay with Hematoxylin and Eosin (HE) staining; The reducing of pulmonary artery remodelling was evaluated by histomorphology assay with HE staining; The proliferation of pulmonary artery smooth muscle cells (PASMCs) was evaluated by immunohistochemistry assays (PCNA and Ki67) and MTT assay. Cell cycle analysis and Weston-blot analysis were also performed in the study. Results: HSYA reduced the mean right ventricular systolic pressure (RVSP) of rats with hypoxic pulmonary arterial hypertension (HPH) in a manner of concentration dependency. It significantly inhibited the PASMCs proliferation and attenuated the remodelling of the pulmonary artery and right ventricular hypertrophy. Conclusion: These findings suggested that HSYA protected against hypoxic induced pulmonary hypertension by reversing the remodelling of the pulmonary artery through inhibiting the proliferation and hypertrophy of PASMCs. This is in accordance with our previous finding that HSYA protects against the pulmonary artery vascular constriction. All these results suggest that HSYA may be a promising candidate for HPH treatment. Graphical abstract: